The Rancang Bangun Sistem Informasi Geografis Pemetaan Lokasi Tambal Ban Menggunakan Framework Laravel dan Algoritma Djikstra - Al Firas Manar, Muhammad Ulin Nuha (JATISI, 2025)
Flat tires during travel are a common issue, especially when drivers are in unfamiliar areas. Although digital maps like Google Maps are widely used, information on tire repair locations remains limited. This study aims to design a web-based Geographic Information System (GIS) that displays real-time locations of tire repair services. The system includes features such as operating hours, service types, and contact details. Development was carried out using the Laravel framework and the Waterfall method, covering stages from communication to testing. GPS technology, Dijkstra’s algorithm, and geofencing are implemented to calculate the fastest route and detect user location. Black Box testing confirms the system functions properly and supports the digitalization of local tire repair services for easier online access.